THE WORK OF PRIMARY HEALTH CARE NURSES IN ONCOLOGY CARE: AN INTEGRATIVE REVIEW - Geize Rocha Macedo de Souza; Luiza Helena de Oliveira Cazola; Renata Palópoli Pícoli (Universidade Federal do Paraná, 2018)
Objective: to identify the role of the primary health care nurses in oncology care, based on scientific literature evidence. Method: this is an integrative review with data collected in October 2017, from four databases, resulting in 117 articles. Based on the established inclusion criteria, seven articles were selected. Results: the articles allowed the organization of results into three thematic categories: six health care activities (86%); four health education activities (57%); and one professional primary health care competence (14%). Final considerations: in oncology nursing care, it is crucial to combine knowledge with clinical practice, centered in holism and individualized follow-up, to allow its involvement in activities related to healthcare, health education, and prevention and control actions in primary health care.